Absorptive capacity in a two-sector neo-Schumpeterian model: a new role for innovation policy. (19th October 2019) - Almudi, Isabel; Fatas-Villafranca, Francisco; Fernández-Márquez, Carlos M; Potts, Jason; Vazquez, Francisco J
Abstract: We propose a new co-evolutionary computational two-sector approach to the design of national innovation policy that recognizes the importance of intersectoral absorptive capacity constraints in innovation linkages between sectors in an economy. We show how the innovative capacity of an upstream producer sector can be constrained by the absorptive capacity of the downstream-user sector. This suggests that the low productivity performance of modern innovation policy might in part be understood as a consequence of sectorally unbalanced knowledge evolution, where the problem lies in underinvestment in innovative capabilities in the downstream sector. Our computational two-sector model suggests an important role for innovation policy to create a balanced, sectorally targeted approach.